Age of danger : keeping America safe in an era of new superpowers, new weapons, and new threats - Hoehn, Andrew R.; Shanker, Thom (Hachette Books, Hachette Book Group, 2023)
"Again and again, American taxpayers are asked to open their wallets and pay for a national security machine that costs $1.25 trillion to operate. How is it possible that the United States Government gets it so wrong on so many critical issues, and so often? And if our expensive national security machine is not working, what can be done? Enter Thom Shanker, best-selling author and former New York Times editor, along with Andrew Hoehn, RAND SVP of Research and Analysis and former Pentagon official, who have not only decades of national security expertise between them, but access to virtually every expert with something valuable to say. Age of Danger looks at the major challenges facing America-from superpowers like Russia and China to emerging threats like pandemics, cybersecurity, climate change, and drones-and reimagines the national security apparatus into something that can truly keep Americans safe. After several decades focused primarily on the imminent threat of terrorism, it is time for America to once again be forward-thinking in its national security before we lose pace with a new generation of threats. Weaving together expert analysis with exclusive interviews from a who's who of national security, including Robert Gates, Stanley McChrystal, Eric Schmidt, and Michael Leiter, Shanker and Hoehn argue that the United States must create an industrial-grade, life-saving machine out of a system that, for too long, was focused only on deterring adversaries and carrying out global military operations. It is a timely and crucial call to action, a call that if heeded, could save Americans lives, money, and our very future on the global stage"--